2016
DOI: 10.1016/j.cad.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Parametric CAD modeling: An analysis of strategies for design reusability

Abstract: CAD model quality in parametric design scenarios largely determines the level of flexibility and adaptability of a 3D model (how easy it is to alter the geometry) as well as its reusability (the ability to use existing geometry in other contexts and applications). In the context of mechanical CAD systems, the nature of the feature-based parametric modeling paradigm, which is based on parent-child interdependencies between features, allows a wide selection of approaches for creating a specific model. Despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 30 publications
0
55
0
Order By: Relevance
“…"Horizontal" modeling minimizes CAD repair by removing parent/child dependencies between features, " Explicit References" modeling minimizes the number of constraints linked to existing geometries by managing functional references, and "Resilient" modeling manages the sequence of the design tree by organizing the features by purpose and priority [12]. The researchers found that "Resilient" modeling was most effective, although the level of CAD expertise of the study population (students) could have affected the results [12].…”
Section: Design Intent Instructionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Horizontal" modeling minimizes CAD repair by removing parent/child dependencies between features, " Explicit References" modeling minimizes the number of constraints linked to existing geometries by managing functional references, and "Resilient" modeling manages the sequence of the design tree by organizing the features by purpose and priority [12]. The researchers found that "Resilient" modeling was most effective, although the level of CAD expertise of the study population (students) could have affected the results [12].…”
Section: Design Intent Instructionmentioning
confidence: 99%
“…We believe that suggestions on how design intent can be enhanced and captured can be arranged into three categories: (1) basic strategies that have been previously suggested by different authors and are generally followed by CAD instructors; (2) strategies that are linked to metrics that can be automated by Model Quality Testers, which rarely include highly semantic quality concepts like those linked to design intent (see for example: [12]), and (3) novel strategies that currently appear in the scientific literature, but remain absent from most of the instruction courses (see [13], [12]). …”
Section: Design Intent Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…They further state that "Explicit References" modeling provides for simple models but are difficult to model and "Resilient" modeling is effective, in spite of reference nodes needed to reduce dependencies [Camba et al, 2014a]. In a more detailed examination, these different modeling methodologies were studied to examine CAD reusability [Camba et al, 2016]. "Horizontal" modeling minimizes CAD repair by removing parent/child dependencies between features, " Explicit References" modeling minimizes the number of constraints linked to existing geometries by managing functional references, and "Resilient" modeling manages the sequence of the design tree by organizing the features by purpose and priority [Camba et al, 2016].…”
Section: Design Intent Instructionmentioning
confidence: 99%
“…In a more detailed examination, these different modeling methodologies were studied to examine CAD reusability [Camba et al, 2016]. "Horizontal" modeling minimizes CAD repair by removing parent/child dependencies between features, " Explicit References" modeling minimizes the number of constraints linked to existing geometries by managing functional references, and "Resilient" modeling manages the sequence of the design tree by organizing the features by purpose and priority [Camba et al, 2016]. The researchers found that "Resilient" modeling was most effective, although the level of CAD expertise of the study population (students) could have affected the results [Camba et al, 2016].…”
Section: Design Intent Instructionmentioning
confidence: 99%